Pengaruh Kadar Air Lapisan Bawah terhadap Kemantapan Perkerasan Paving di Kawasan Delta Area - Mudiyono, Rachmat; Rosantika, Arga (Pondasi, 2023)
Abstract Geomorphologically, the city of Semarang is formed from the delta formation of the Kaligarang River, if the water discharge increases, it is certain that inundation will occur along the river. In addition, puddles caused by high tides are also common. The rapid growth of the city greatly affects the availability of supporting infrastructure such as roads. The age of pavement planning in the city of Semarang is often not reached due to the condition of the flood disaster. The purpose of this study is to determine the level of resistance of the subsurface layer to water which will affect the stability of the paving pavement. The initial stages carried out were the preparation of a research proposal containing the preparation of tools and materials, literature studies and the design of primary and secondary data collection instruments, the next stage was making laboratory test samples and conducting hydraulic test analysis to determine the optimum water content, the end of this activity stage was the formulation conclusion. Based on the results of the analysis, it was found that the water content greatly affects the depth of subsidence, the higher the water content, the higher the decrease. It was proven by testing in the lab, the water content in the base course was 10% sinking 40 mm, 20% 80 mm and 30% 120 mm. Keywords: delta areas; water content; hydraulic test; paving stability AbstrakSecara geomorfologi kota Semarang terbentuk dari formasi delta Sungai Kaligarang apabila debit air meningkat maka bisa dipastikan genangan akan terjadi di semapadan sungai tersebut. Selain itu genangan yang disebabkan oleh rob air laut pasang juga sering dijumpai. Pertumbuhan kota yang semakin pesat sangat berpengaruh terhadap ketersediaan infrastruktur penunjang seperti jalan. Usia perencanaan perkerasan di Kota Semarang sering tidak tercapai karena adanya kondisi bencana genangan air. Tujuan dari penelitian ini adalah mengetahui tingkat ketahanan lapisan bawah permukaan terhadap air yang nantinya akan berpengaruh pada kemantapan perkerasan paving. Tahapan awal yang dilakukan adalah penyusunan proposal penelitian yang memuat persiapan alat dan bahan, studi literatur dan desain instrumen pengumpulan data primer dan sekunder, tahap selanjutnya membuat sampel pengujian laboratorium dan melakukan analisis uji hidrolis untuk mengetahui kadar air optimum, akhir dari tahapan kegiatan ini adalah perumusan kesimpulan. Berdasarkan hasil analisis didapatkan bahwa kadar air sangat mempengaruhi dalamnya amblesan, semakin banyak kadar airnya semakin tinggi penurunannya. Dibuktikan dengan pengujiuan di lab, kadar air pada base course 10% ambles 40 mm, 20% 80 mm dan 30% 120 mm. Kata kunci: delta area; kadar air; uji hidrolis; kemantapan paving.